On the thermal spalling mechanism of reactive powder concrete exposed to high temperature: Numerical and experimental studies. (July 2016) - Ju, Yang; Liu, Jinhui; Liu, Hongbin; Tian, Kaipei; Ge, Zhishun
Highlights: Numerical and experimental studies of RPC's thermal spalling. Quantitative characterization of the interior temperature, heat transfer, stress field and failure mechanism of thermal spalling. The experimentally measured thermophysical parameters of RPC are adopted in the simulation. A conceptual model is developed to elucidate the thermal spalling mechanism. Abstract: Concrete spalling at high temperature seriously jeopardizes the integrity of the entire structure. Many explanations for the spalling risk exist, but few models can accurately predict it. A numerical approach to quantitatively characterizing the intrinsic mechanism that governs the devastating spalling of RPC at high temperature is presented. The proposed model is implemented in COMSOL MULTIPHYSICS, and the finite element method is employed as the basic stress analysis tool. The maximum tensile stress criterion and the distortion energy density theory are utilized as the spalling failure thresholds. The interior temperature field, stress field, spalling distribution and evolution of RPC are analyzed accordingly. It is shown that the numerical simulation results are in good agreement with the experimental observations of RPC's spalling. A conceptual model is proposed to elucidate the mechanism that induces the progressive spalling failure of RPC based on the numerical and experimental results.